Isolation and characterization of Streptococcus from dental plaque samples - Chan, Weng Yee (2015)
Dental caries is still a prevalent chronic condition that affecting health in the worldwide population. Other oral diseases, such as infection and tooth loss, are also very common. These diseases normally associated with discomfort and pain, eating and speech difficulties. Periodontal disease is an inflammatory infection on the gums, connective tissues and jaw bone that support the teeth. The root of these complications is formation of dental plaque by specific group of bacteria. Prevention practices, such as brushing teeth twice a day, using dental floss and antibacterial rinse, eating a balanced diet are not practiced. Therefore, the most efficient method to overcome this issue is eliminating the causative agents. This study is to isolate and characterize dental plaque causing bacteria. The bacteria were isolated from dental plaque sample. Preliminary identifications performed were macroscopic, microscopic morphology and biochemical tests. The bacteria isolated were characterized using Restriction Fragment Length Polymorphism (RFLP) and DNA sequencing. Three isolates were selected and identified as Streptococcus mitis and Streptococcus oralis.